Wage Gaps and Development : Lessons from U.S. History - Mourmouras, Alex (IMF Working Papers; Working Paper ;, 2007)
During the course of development, wages and labor productivity are much higher in the nonfarm sectors of the economy than in agriculture. In this paper, we examine the sources and consequences of wage and productivity gaps in the U.S. from 1800 to 2000. We build a quantitative general equilibrium model that closely matches the two-century long paths of farm and non-farm labor productivity growth, schooling, and fertility in the U.S. The family farm emerges as an important institution that contributes to differences in wages and labor productivity. Income from farm ownership compensates farm workers for the relatively low labor productivity and wages earned in agriculture. Farm ownership, along with the higher cost of raising children off the farm, generated a two-fold gap in labor productivity across the farm and nonfarm sectors in the 19th century US. Consequently, the reallocation of labor from farming to industry raised the average annual growth rate of output per worker by about half a percentage point over the 19th century. The paper also draws some lessons from the quantitative analysis of U.S. economic history for currently developing countries.